Blockchain Implications for Marketing; A Review and an Empirical Analysis - Taher M. Al-Ahwal; Dušan Mladenović; Ahad ZareRavasan (Journal of Information Technology Management)
Blockchain technology was initially implemented for cryptocurrencies in 2009, but it caught the undivided attention of multiple industries such as finance, supply chain management, healthcare, and governments. This research was set out to investigate and evaluate six benefits of blockchain for marketing: fostering disintermediation, combating click fraud, reinforcing trust and transparency, enhancing privacy protection, empowering digital marketing security, and enabling creative loyalty programs. An empirical study in the form of an online survey was conducted to examine the realization of benefits in practice. The research concluded that blockchain does indeed provide promising benefits for marketing, but that depends on whether marketers use public (permissioned) blockchain or private (permissioned) blockchain, and also the ability of the blockchain community to resolve fundamental challenges and pending issues such as scalability, speed, interoperability, and privacy, besides several many others.